Телесериалы как интерактивный способ обучения английскому языку - Клеблеева Резеда, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
TV series are a popular tool for learning English because they allow students to immerse themselves in a real context and hear live speech. This article examines the role of television series in improving language skills such as listening, vocabulary and grammar. Special attention is paid to how television series can be used to explore the cultural aspects of language and increase student motivation. Examples of the use of TV series for educational purposes are presented, as well as recommendations for the effective implementation of this method in the educational process.